Turning point for America : - Werstein, Irving (Julian Messner, 1964)
As the nineteenth century drew to a close, the United States reached the end of its own frontiers. The time had come to find new markets for American products and to enter the global picture as a growing power. At the same time, in Cuba the tyrannical rule of the dying Spanish Empire inflicted incredible cruelties on the Cuban people who were struggling to gain their freedom.